2000
DOI: 10.2460/ajvr.2000.61.162
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the phenotypes of Streptococcus zooepidemicus isolated from tonsils of healthy horses and specimens obtained from foals and donkeys with pneumonia

Abstract: An SzP-specific immunoblot is a useful, sensitive measure of diversity among strains of S. zooepidemicus. Single strains with SzP phenotypes similar to those found in tonsils of healthy horses cause pneumonia. Because of the diversity of SzP phenotype and genotype among isolates from animals with pneumonia, SzP phenotype is not an important determinant of invasiveness or epizootic capabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
55
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 12 publications
1
55
0
2
Order By: Relevance
“…zooepidemicus) of Lancefield group C is a normal tonsillar and mucosal commensal of the upper respiratory tract of Equus spp. Although a variety of serovars are present in the tonsils of healthy horses, respiratory disease is associated with a single clone, which usually is present in large numbers in bronchial and nasopharyngeal secretions (1). Unlike its clonal derivative Streptococcus equi, comparisons of the genomic sequences of S. zooepidemicus in databases confirm genetic variability and extensive rearrangement/recombination, as suggested by early studies (2,3).…”
mentioning
confidence: 72%
“…zooepidemicus) of Lancefield group C is a normal tonsillar and mucosal commensal of the upper respiratory tract of Equus spp. Although a variety of serovars are present in the tonsils of healthy horses, respiratory disease is associated with a single clone, which usually is present in large numbers in bronchial and nasopharyngeal secretions (1). Unlike its clonal derivative Streptococcus equi, comparisons of the genomic sequences of S. zooepidemicus in databases confirm genetic variability and extensive rearrangement/recombination, as suggested by early studies (2,3).…”
mentioning
confidence: 72%
“…Walker, R. L. et al investigated the association of SzP protein variations in S. zooepidemicus with clinical manifestations of infection in horses, but no relationship was seen [9]. We have also previously reported that there were no differences in SzP types between isolates from healthy tonsils and isolates from lesions in pneumonia cases [1,2]. However, the SzP protein appears to be a pathogenic factor in S. zooepidemicus [10] and clearly has different types [this paper].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we compared the SzP protein and the genes from healthy horses with those from foals and donkeys with pneumonia [2]. The results showed the tonsils of every healthy horse to be colonized by a range of SzP phenotypes similar to those in foals or donkeys with pneumonia, even though numerous isolates from animals with pneumonia had a single SzP phenotype, indicating infection by a single strain or clone.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Multilocus sequence typing (MLST) of isolates from persistent outbreaks in a United Kingdom shelter revealed the predominance of sequence type 10 (ST-10) from 1999 to 2002 and ST-62 from 2007 to 2010 (6). The clonality of shelter epizootics of S. zooepidemicus pneumonia in dogs contrasts with the situation usually observed in horses, in which a single serovar randomly derived from multiple serovars in the tonsillar complex is aspirated and infects the lower respiratory tract devitalized by virus infection or extended transportation (7). However, outbreaks of equine respiratory disease caused by specific clones of S. zooepidemicus are occasionally observed (8,9).…”
mentioning
confidence: 72%